Privatization Policy and Rural Development: An Assessment of Power Holding Company of Nigeria in Ijumu Local Government of Kogi State (Journal of International Studies, 2017)
The state of electricity supply in Nigeria is nothing to write home about. The situation has resulted in the government adopting the privatization policy as the elixir to the affliction of inadequate power supply in the country. Thus, this paper investigated the privatization policy of the power sector and how it affects development in the rural areas of the Ijumu local government of Kogi State, Nigeria. The modernization theory was adopted in this paper. Data acquired from 120 respondents selected with the use of the three-stage sampling procedure, was analyzed with Statistical Packages for Social Sciences (SPSS/PC) Version 20. The study revealed that privatization of the power sector has not transformed into a significant improvement in electricity supply. Consequently, the study recommends that there is need for the government to ensure that the policy adopted should be of optimum form to achieve the desired results.